GELOMBANG GRAVITASI DENGAN LATAR SCHWARZSCHILD - , MUKSIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gravitational waves have a significant role in physics. The challenge is that the gravitational waves are so difficult to detect because of its weakness. The metric of gravitational waves has been derived by using the perturbation on the Minkowski metric as the first step to understand and to detect the gravitational waves. Then the Schwarzschild metric is also used to detect the gravitational waves.